2013
DOI: 10.1111/jeb.12256
|View full text |Cite
|
Sign up to set email alerts
|

The oxidative costs of territory quality and offspring provisioning

Abstract: The costs of reproduction are an important constraint that shapes the evolution of life histories, yet our understanding of the proximate mechanism(s) leading to such life-history trade-offs is not well understood. Oxidative stress is a strong candidate measure thought to mediate the costs of reproduction, yet empirical evidence supporting that increased reproductive investment leads to oxidative stress is equivocal. We investigated whether territory quality and offspring provisioning increase oxidative stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…This may indicate that securing privileged access to mates, which comprises guarding, courtship and vocalization behaviours, implies higher pre-copulatory investment, such as higher metabolism and elevated cellular detoxification, but does not generate excessive lipid peroxidation in harem males (Alonso- Alvarez et al 2007;Guindre-Parker et al 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may indicate that securing privileged access to mates, which comprises guarding, courtship and vocalization behaviours, implies higher pre-copulatory investment, such as higher metabolism and elevated cellular detoxification, but does not generate excessive lipid peroxidation in harem males (Alonso- Alvarez et al 2007;Guindre-Parker et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…They may also endure repetitive injuries during contest, leading to immune responses such as antimicrobial defences and inflammations. These higher reproductive expenditures are expected to induce oxidative costs (Guindre-Parker et al 2013;Costantini 2014) and favour the allocation of more antioxidants to somatic functions related to pre-copulatory competition and hence less to the protection of sperm cells.…”
Section: Introductionmentioning
confidence: 99%
“…Also, lower red blood cell resistance to oxidative burst and higher levels of oxidative damage in lipids and proteins before pair formation or during courtship or incubation have been associated with smaller litter size at birth in laboratory mice (Stier et al, 2012), decreased male parental effort in Florida scrub jays (Heiss and Schoech, 2012), smaller clutch size, lower female hatching probability and lower male survival probability to the next reproductive event in alpine swifts (Bize et al, 2008), and a decline in lifetime total breeding events and greater aging rate in captive zebra finches (Kim et al, 2009). However, no association between oxidative markers upon arrival to the courting site and territory quality or number of fledglings produced by snow buntings was found (Guindre-Parker et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Various studies in wild animals have found the predicted positive associations between reproduction, daily energy consumption and oxidative damage in lipids and proteins (Bergeron et al, 2011;Heiss and Schoech, 2012;Fletcher et al, 2013;Costantini et al, 2014). Furthermore, studies in wild and captive animals have found evidence of a potential oxidative imbalance resulting from reproduction, including higher production of reactive oxygen metabolites (Casagrande et al, 2012;Stier et al, 2012;Guindre-Parker et al, 2013), decreased antioxidant capacity (Wiersma et al, 2004;Costantini et al, 2010;van de Crommenacker et al, 2011) and diminished resistance to rapid temporary ROS overproduction (Alonso-Alvarez et al, 2004;Bertrand et al, 2006;Losdat et al, 2011;Christe et al, 2012). Nevertheless, other studies have failed to find a relationship between reproductive effort and oxidative damage (Nussey et al, 2009;Isaksson et al, 2011a,b;Aloise-King et al, 2013;Wegmann et al, 2015), have found increased antioxidant response in females' liver cells during parental care (Yang et al, 2013;Xu et al, 2014), or have found less oxidative damage in serum, liver, kidney and muscle cells of reproductive compared with non-reproductive individuals (Garratt et al, 2011Ołdakowski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Reproduction can also affect oxidative status. High energy investment during reproduction has been linked with a decreased resistance to oxidative stress [37], decreased antioxidant defences [38, 39] and an increased oxidative stress [40, 41]. There can also be resource allocation trade-offs in reproductively active individuals [42] leading to a lower immunocompetence (i.e.…”
Section: Introductionmentioning
confidence: 99%